Specyfika skali ważonych ocen - Ubermanowicz, Stanisław (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
The author describes the essence and characteristics of the novel surveying evaluation scale of the educational process. Balancing between quality, intensity and conclusiveness of expressions is a selective clue to choose indicators i.e. stimulus ascertainments to the survey. On the basis of empirical studies of "Informatics Culture" (computer experience and cognizance) the author discusses quantitative parameters of the scale and the way of representing them in practice. Special attention was paid to a contextual representation of results, to the vector method of the appraisal value of alteration in time; and to the issues of inter-group comparability of the process effects.
Keywords: skala ważona; ewaluacja; metodologia; statystyka; badania; Weighted Rating Scale; evaluation; methodology; statistic; research; Neodidagmata